Effect of Breathing Exercises on Lung Volumes and Fatigue in Chemical Victims - Z. Ahmadi; M. Moradi; B. Abedi (Afarand Scholarly Publishing Institute, 2016)
Aims: One of the three main organs undergone the most injuries and side-effects due to the mustard sulfur is the lung. The effects of the breathing exercises on such side-effects have been studied. The aim of the present study was to investigate the effects of the breathing exercises on the lung volume and the fatigue in the chemically injured veterans. Materials & Methods: In the semi-experimental study, 23 veterans with pulmonary chemical injuries and a history of exposure to the mustard sulfur were studied in Arak Township in 2015. The subjects, selected via the purposeful available sampling method, were randomly divided into two groups including experimental (n=13) and control (n=10) groups. An 8-week breathing exercise program was conducted in experimental group. The program consisted of three 30- to 45-minute stacked-lip and diaphragmatic breathing sessions per week. The lung function and the fatigue severity were assessed before and after the intervention. Data was analyzed by SPSS 21 software using paired T test and one-way covariance analysis. Findings: The breathing exercises in experimental group significantly increased the lung indices and significantly reduced the mean fatigue level (p<0.05). Nevertheless, no significant difference was observed between the pretest and posttest results in control group (p>0.05).   Conclusion: The breathing exercises can improve the breathing pattern and reduce the fatigue level in the chemically injured veterans.